HUBUNGAN USIA, INDEKS MASA TUBUH, DAN GRAVIDA PADA IBU HAMIL DENGAN PREEKLAMPSIA DI RUMAH SAKIT MUHAMMADIYAH SURABAYA: RELATIONSHIP OF AGE, BODY INDEX, AND GRAVIDA IN PREGNANT WOMEN AND PREECLAMPSIA IN MUHAMMADIYAH HOSPITAL SURABAYA - maya rafida maya rafida (Surabaya Biomedical Journal, 2022)
Preeclampsia is one of the causes of increased maternal mortality and morbidity, based on the Republic of Indonesia Ministry of Health data in 2016, the maternal mortality rate in East Java Province reached 91.00 per 100,000 live births. The highest cause of maternal death in 2016 was preeclampsia / eclampsia, which was 30.90% or as many as 165 people. Preeclampsia can appear at more than 20 weeks' gestation marked by hypertension and accompanied by proteinuria. This study aims to determine the relationship of age, body mass index, and gravida to pregnant women who have preeclampsia at Muhammadiyah Hospital in Surabaya. This type of research uses a cross sectional study, sample selection using total sampling with a minimum sample of 70 samples. Large samples obtained 210 respondents, as many as 105 experienced preeclampsia and 105 respondents did not experience preeclampsia. Based on the results of bivariate statistical tests found age is a risk factor for the incidence of preeclampsia (p: 0.039 <0.05), body mass index is associated with the incidence of preeclampsia (p: 0.002 <0.05) and gravida has no relationship with the incidence of preeclampsia (p: 0.410 > 0.05). Based on the multivariate test, there was an influence of age 36-45 years on the incidence of preeclampsia with a risk of 4.060 times experiencing preeclampsia compared to the age of 20-35 years, obese affected the incidence of preeclampsia with a risk of 4.696 times experiencing preeclampsia compared to normalweight and gravida influencing the incidence of preeclampsia with a risk of 2,099 times experiencing preeclampsia. The conclusion of this research is that there is a relationship between age, body mass index and gravida in preeclampsia at Muhammadiyah Hospital in Surabaya.